Correlation between patient weight and defects in DNA mismatch repair: is this the link between an increased risk of previous cancer in thinner women with endometrial cancer?. Issue 1 (1st January 2008) - Cohn, D. E.; Pavelka, J. C.; Frankel, W. L.; Morrison, C. D.; Hampel, H.; Copeland, L. J.; Fowler, J. M.
Abstract : The objective is to determine the relationship between obesity and defects in DNA mismatch repair (MMR) in women with endometrial cancer and to establish whether our previous finding of a higher rate of previous malignancy in thinner women with endometrial cancer is related to these factors. Specimens from 109 patients with primary uterine cancer were used to create a tissue microarray, which was stained with antibodies against MMR genes MLH1, MSH2, MSH6, and PMS2 . Genotyping of normal and tumor tissues for microsatellite instability (MSI) was performed. Patients were stratified by body mass index (BMI) and correlated with a history of previous malignancy and defects in MMR. The average BMI of the overall population was 33 kg/m 2 . Defective MMR was seen in 22% of tumors. The mean BMI in patients with tumors with MSI was 30.5, compared with 33.8 in microsatellite stable (MSS) tumors ( P = 0.06); MSS tumors were more commonly seen in patients with a BMI more than 40 (25% vs 5% in patients with tumors with MSI, P = 0.07). Prior to their diagnosis of endometrial cancer, 16/109 (15%) patients reported having a prior malignancy, 11 (69%) had breast cancer, and 1 had colorectal cancer. Patients with tumors with MSI had previous cancer in 17% of cases, compared with 14% of patients with MSS tumors ( P = 0.75). Our previous finding of an increased rate of prior malignancy in thinner patients with endometrial cancer does not appear to be due to alterations in MMR, and hereditary nonpolyposis colorectal cancer–associated cancers are rarely the prior malignancy.